Editor's Choice-Medically managed patients with non–ST-elevation acute myocardial infarction have heterogeneous outcomes, based on performance of angiography and extent of coronary artery disease. Issue 3 (April 2017) - Feldman, Laurent; Steg, Philippe G; Amsallem, Myriam; Puymirat, Etienne; Sorbets, Emmanuel; Elbaz, Meyer; Ritz, Bernard; Hueber, Arnaud; Cattan, Simon; Piot, Christophe; Ferrières, Jean; Simon, Tabassome; et al.
Background: Medically managed individuals represent a high-risk group among patients with non–ST-elevation acute myocardial infarction (NSTE-AMI). We hypothesized that prognosis in this group is heterogeneous, depending on whether medical management was decided with or without coronary angiography (CAG). Methods: Using data from the French Registry of Acute ST-Elevation or Non–ST-Elevation Myocardial Infarction (FAST-MI), we analysed data from 798 patients with NSTE-AMI who were medically managed (i.e. without revascularization during the index hospitalization). Patients were categorized according to the performance of CAG and, if performed, to the extent of coronary artery disease (CAD). Results: There were marked differences in baseline demographics, according to whether CAG was performed and to the extent of CAD. While the overall mortality rate at five years was high (56.2%), it differed greatly between groups, with patients who did not undergo CAG having a higher mortality rate (77.4%) than patients who underwent CAG (36.7%, p <0.001), and a higher mortality rate even than patients with multivessel CAD (54.2%, p <0.001). By multivariable analysis, non-performance of CAG was an independent predictor of all-cause mortality among medically managed NSTE-AMI patients (adjusted hazard ratios (95% confidence intervals) 3.19 (1.79–5.67) at 30 days, 2.28 (1.60–3.26) at one year, and 1.63 (1.28–2.07) at five years; all p <0.001). Conclusion: Medically managed patients with NSTE-AMI are a heterogeneous group in terms of baseline characteristics and outcomes. The highest risk patients are those who do not undergo CAG. Non-performance of CAG is a strong predictor of death. (FAST-MI, NCT00673036).